A Frame for Fiction: On Galo Ghigliotto’s El Museo de la Bruma - Téllez, Jorge (Intermédialités / Intermediality, 2024)
In this article, I study two tropes with a long-standing tradition in Latin American fiction: museums and machines. Specifically, I analyze Galo Ghigliotto’s 2019 novel El museo de la bruma from a two-fold perspective. First, as an example of a larger corpus of contemporary fiction that has taken to material culture as a refuge for storytelling in a world where the digital increasingly mediates the human experience. Second, in relation to a reference made in the book to Adolfo Bioy Casares’s 1940 fictional character Morel as the main architect of the museum. Some of the questions I explore in this article are: how does the relationship between ekphrasis and collective memory work? How does the body regulate the framing of memories regarding the catalog depicted in the novel? If, in Bioy Casares’s novel, the machine is the trope that destabilizes reality by duplicating a body, what happens with the incorporation of this fiction eighty years later in Ghigliotto’s novel when the digital realm has become (or threatens to become) reality? How is contemporary fiction responding to this change?